The roles of intrarenal 20-hydroxyeicosatetraenoic and epoxyeicosatrienoic acids in the regulation of renal function in hypertensive Ren-2 transgenic rats - Certíková Chábová, Vera; Kramer, Herbert J; Vanecková, Ivana; Thumová, Monika; Skaroupková, Petra; Tesar, Vladimír; Falck, John R; Imig, John D; Cervenka, Ludek (Kidney & blood pressure research, 2007)
BACKGROUND: The present study was performed in hypertensive Ren-2 transgenic rats (TGR) and in normotensive Hannover Sprague-Dawley (HanSD) rats. First, the intrarenal protein expression of CYP4A, the enzyme catalyzing the formation of 20-hydroxyeicosatetraenoic acid (20-HETE), and of CYP2C23, the enzyme responsible for epoxyeicosatrienoic acid (EET) production, was evaluated. Second, the renal functional responses to inhibition of the intrarenal formation of 20-HETE and EETs were investigated. METHODS: Renal hemodynamics and electrolyte excretion were evaluated in response to the administration of inhibitors of 20-HETE and EET formation into the renal artery. In renal cortical tissue, CYP4A and CYP2C23 protein expression was assessed by Western blot analysis. Urinary concentrations of 20-HETE and EETs were measured using a fluorescent HPLC assay. RESULTS: TGR have higher kidney CYP4A protein expression and urinary 20-HETE excretion but significantly lower CYP2C23 protein expression and urinary EET excretion than HanSD. Intrarenal inhibition of 20-HETE and EET formation decreased sodium excretion in HanSD, whereas inhibition of 20-HETE increased urinary excretion of sodium in TGR without altering renal hemodynamics. CONCLUSIONS: Our data suggest that in TGR, deficient intrarenal synthesis of EETs combined with increased synthesis of 20-HETE with its stimulation of tubular sodium absorption may contribute to the development of hypertension in TGR.
Keywords: hypertenze; Male; Animals; kyseliny hydroxyeikosatetraenové; krevní tlak; mužské pohlaví; krysa rodu Rattus; Kidney; Hydroxyeicosatetraenoic Acids; Blood Pressure; Rats; Rats, Sprague-Dawley; zvířata; Animals, Genetically Modified; geneticky modifikovaná zvířata; potkani Sprague-Dawley; kyseliny arachidonové; ledviny; Arachidonic Acids; Hypertension